2018
DOI: 10.1111/apt.15058
|View full text |Cite
|
Sign up to set email alerts
|

Combining hepatitis B core‐related and surface antigens at end of nucleos(t)ide analogue treatment to predict off‐therapy relapse risk

Abstract: Summary Background There remains an unmet need for convenient biomarkers to assess the risks of discontinuing nucleos(t)ide analogues (NAs) in chronic hepatitis B (CHB). Aim To investigate if hepatitis B core‐related antigen (HBcrAg) is an independent of surface antigen (HBsAg) for risk prediction of NA cessation. Methods This prospective multicentre study enrolled 135 CHB patients who stopped entecavir or tenofovir after achieving viral remission for a median of 25.2 months. All patients stopped NA with negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(147 citation statements)
references
References 34 publications
6
131
4
1
Order By: Relevance
“…https://orcid.org/0000-0002-1657-010X Recent studies have shown that HBcrAg and serum GGT levels are significant predictors of HBV relapse after discontinuing NA therapy. 3,4 However, the HBcrAg assay is not available in Taiwan, and serum GGT was not checked routinely in our study. Thus, we could not provide these data after cessation of either ETV or TDF therapy.…”
Section: Chao Wumentioning
confidence: 97%
See 1 more Smart Citation
“…https://orcid.org/0000-0002-1657-010X Recent studies have shown that HBcrAg and serum GGT levels are significant predictors of HBV relapse after discontinuing NA therapy. 3,4 However, the HBcrAg assay is not available in Taiwan, and serum GGT was not checked routinely in our study. Thus, we could not provide these data after cessation of either ETV or TDF therapy.…”
Section: Chao Wumentioning
confidence: 97%
“…2 Furthermore, serum gamma-glutamyl transferase (GGT) levels at treatment start and at HBeAg seroconversion were also reported to impact the clinical relapse for CHB patients after nucleos(t)ide analogue cessation. 3 However, the levels of HBcrAg and GGT in CHB patients in the ETV and TDF groups were not provided by the authors. 1 Multicenter prospective cohort studies with large sample size are still needed to confirm whether HBV relapse occurs sooner and is more severe after TDF cessation than after the cessation of ETV in CHB patients.…”
Section: Editorsmentioning
confidence: 99%
“…Therefore, baseline HBcrAg measurements may help clinicians prescribe preventive treatment if the presence of HBcrAg can be confirmed. Many studies have shown that HBcrAg can predict the development of HCC and the outcome of NA therapy . However, few studies have focused on the relationship between HBcrAg levels and HBV recurrence after LT. Yasunaka et al first reported on this relationship, and found that HBcrAg levels were linearly correlated with post‐LT cccDNA levels .…”
Section: Discussionmentioning
confidence: 99%
“…At baseline, 337 (13.9%) of the 2433 patients with cirrhosis (information of cirrhosis was not reported in two studies [24,27], including 140 off-NAs patients), which was diagnosed by histology ndings and/or imaging studies. [32], entecavir in three [23,24,28], tenofovir in two [20,34], several NAs in fteen [19,21,22,26,30,31,33,[35][36][37][38][39][40][41]44], and NAs was not reported in the remaining ve studies [25,27,29,42,43] ( Table 1).…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…As to the three studies [32,36,37] provided more than one de nition of VR, when calculating the overall pooled rates of VR, we adopted the de nition of VR based on HBV DNA level >2000 IU/mL. BR after NAs cessation was de ned as ALT above the upper limit of normal (ULN) in three [24,31,41], >1.2 ULN in one [20], and >2 ULN in fteen studies [19,22,[25][26][27][28][29][32][33][34][35]38,39,43,44]. One study speci ed two de nitions of BR which were based on ALT >ULN and > 2 ULN [36].…”
Section: Studies Characteristicsmentioning
confidence: 99%